EVALUASI KEBIJAKAN PERATURAN DAERAH KOTA SEMARANG NOMOR 11 TAHUN 2000 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI PEDAGANG KAKI LIMA SIMPANG LIMA SEMARANG - Christine Gitta Candra Puspita; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2016)
High unemployment and the increasing urbanization made bigger informal activity by the community Semarang city. The activity of informal done to look as income is vendors. Number of street vendors Semarang city from year to year continue to rise. So it appeared problems environment and town planning makes government Semarang city issued a policy regulation in Semarang number 11 years 2000 on the regulation and development street vendors. The purpose of this research is to evaluate the achievement of a goal policy by law regulations and development on the street vendors simpang lima semarang and to know the implementation of a policy of the regulation. This research using type descriptive with a qualitative approach. Technique data collection used the observation, interview, study documentation and the literature study. This research result indicates that the implementation of a policy on setting and development street vendors Simpang Lima Semarang operated quite well. There are still some transgression committed street vendors in their activities and had brought a permit or identity card street vendors Simpang Lima of government officials. Need to an increase in socialization regarding the regulations and training street vendors to the street vendors Simpang Lima policy that the purpose of this regulation can be achieved.